2013
DOI: 10.1257/app.5.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Campaign Contributions over CEOs' Careers

Abstract: Individuals dominate money in politics, accounting for over 90 percent of campaign contributions, yet studies of drivers of individuals' giving are scarce. We analyze data on all contributions made between 1991 and 2008 by all 1,556 people who became S&P 500 CEOs during that interval. We exploit variation in leadership status over these individuals' careers to identify that being an S&P 500 CEO causes a $4,029 or 137 percent jump per election cycle in personal giving. While some fraction of CEOs' contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 48 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…Gordon, Hafer, and Landa (2007) identify a robust relationship between political giving and the sensitivity of compensation to company performance. Fremeth, Schaufele, and Richter (2013) similarly find that being promoted to CEO of a S&P 500 company is associated with an increase in the total amount donated beyond what would be expected from increased earnings alone. 7 Although these studies identify conditions that lead executives to spend more on politics, none directly considers whether these same incentives also influence decisions about how to allocate their funds.…”
Section: Political Spending By Corporate Elitesmentioning
confidence: 77%
“…Gordon, Hafer, and Landa (2007) identify a robust relationship between political giving and the sensitivity of compensation to company performance. Fremeth, Schaufele, and Richter (2013) similarly find that being promoted to CEO of a S&P 500 company is associated with an increase in the total amount donated beyond what would be expected from increased earnings alone. 7 Although these studies identify conditions that lead executives to spend more on politics, none directly considers whether these same incentives also influence decisions about how to allocate their funds.…”
Section: Political Spending By Corporate Elitesmentioning
confidence: 77%
“…Second, CEOs (along with other executives and directors) are far less pragmatic and access oriented than their corporate PACs in their giving: they are more ideological, are more likely to give to nonincumbents, and are less likely to give to incumbents with greater organizational power than their firms' affiliated PACs (Bonica 2014). Third, there is little evidence that the ideologically focused nature of CEOs' campaign contributions changes upon assuming their new positions, suggesting they do not see a need, beyond contributing greater sums of money, to alter their personal political behavior for their new organizations' benefit (Fremeth et al 2013). Despite these arguments in favor of using new CEO ideology as an instrument, since the model is exactly identified (i.e., there is only one instrument for the endogenous regressor), there is no formal test for the exogeneity of the instrument, and we can only rely on the logic of the above arguments to establish exogeneity.…”
Section: Attempting To Account Formentioning
confidence: 99%
“…To conduct this analysis, I use data from Fremeth et al (2013), who gathered and processed FEC records on CEOs at S&P 500 firms. For identification purposes, I restrict the sample in this analysis to those firms that hired a new CEO during this time period, and I measure CEO liberalism by calculating the proportion of the new CEO's contributions that went to Democratic candidates in three cycles prior to Downloaded from informs.org by [128.6.218.72] on 18 August 2015, at 17:11 .…”
Section: Attempting To Account Formentioning
confidence: 99%
“…The average value is 7.4 intervenors (with a standard deviation of 6.2) though there is considerable variation among firms: for instance, UNS Electric in Arizona confronted five or fewer intervenors during its rate reviews, but Commonwealth Edison in Illinois faced up to 60 intervenors contesting its rate applications, ranging from public consumer advocates to industrial 8 Prior research on corporate political campaign contribution strategy has typically included only PAC contributions. Here we additionally include contributions by the top management team since recent studies have found they complement PAC contributions (Fremeth et al 2013(Fremeth et al , 2016. In addition, some states limit PAC contributions but not individual contributions, while other states limit the latter but not the former.…”
Section: Empirical Designmentioning
confidence: 99%